In vivo preservation of the hybrid layer by chlorhexidine - Carrilho, M. R. O.; Geraldeli, S.; Tay, F.; Goes, M. F. de; Carvalho, R. M.; Tjäderhane, L.; Reis, A. F.; Hebling, J.; Mazzoni, A.; Breschi, L.; Pashley, D. (SAGE Publications, 2007)
Host-derived proteases have been reported to degrade the collagen matrix of incompletely-resin-infiltrated dentin. This study tested the hypothesis that interfacial degradation of resin-dentin bonds may be prevented or delayed by the application of chlorhexidine (CHX), a matrix metalloproteinase inhibitor, to dentin after phosphoric acid-etching. Contralateral pairs of resin-bonded Class I restorations in non-carious third molars were kept under intra-oral function for 14 months. Preservation of resin-dentin bonds was assessed by microtensile bond strength tests and TEM examination. In vivo bond strength remained stable in the CHX-treated specimens, while bond strength decreased significantly in control teeth. Resin-infiltrated dentin in CHX-treated specimens exhibited normal structural integrity of the collagen network. Conversely, progressive disintegration of the fibrillar network was identified in control specimens. Auto-degradation of collagen matrices can occur in resin-infiltrated dentin, but may be prevented by the application of a synthetic protease inhibitor, such as chlorhexidine.
Keywords: Chlorhexidine; Degradation; Etch-and-rinse adhesive; Hybrid layer; In vivo; MMP; bisphenol A bis(2 hydroxypropyl) ether dimethacrylate; chlorhexidine; dentin bonding agent; fibrillar collagen; matrix metalloproteinase; phosphoric acid; proteinase inhibitor; resin; single bond; unclassified drug; chemistry; dental acid etching; dental bonding; dental surgery; dentin; drug antagonism; human; materials testing; mechanical stress; methodology; surface property; tensile strength; time; transmission electron microscopy; ultrastructure; Acid Etching, Dental; Bisphenol A-Glycidyl Methacrylate; Composite Resins; Dental Bonding; Dental Restoration, Permanent; Dentin; Dentin-Bonding Agents; Fibrillar Collagens; Humans; Materials Testing; Matrix Metalloproteinases; Microscopy, Electron, Transmission; Phosphoric Acids; Protease Inhibitors; Stress, Mechanical; Surface Properties; Tensile Strength; Time Factors